Therapeutic Potential of Hispidin—Fungal and Plant Polyketide - Kseniia A. Palkina; Daria A. Ipatova; Ekaterina S. Shakhova; Anastasia V. Balakireva; Nadezhda M. Markina (Journal of Fungi, 2021)
There is a large number of bioactive polyketides well-known for their anticancer, antibiotic, cholesterol-lowering, and other therapeutic functions, and hispidin is among them. It is a highly abundant secondary plant and fungal metabolite, which is investigated in research devoted to cancer, metabolic syndrome, cardiovascular, neurodegenerative, and viral diseases. This review summarizes over 20 years of hispidin studies of its antioxidant, anti-inflammatory, anti-apoptotic, antiviral, and anti-cancer cell activity.